Development of Interactive Multimedia Learning for Arts and Culture Based on Location Policy in Musi Banyuasin Elementary School - Khusnul Khotimah; Makmun Raharjo; Farhan Yadi; Abd Halim, Noor Dayana (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2025)
This study aims to develop and produce interactive multimedia learning This study aims to develop interactive multimedia learning for Arts and Culture integrated with Senjang local wisdom for elementary school students in Musi Banyuasin and to determine its validity, practicality, and effectiveness in improving learning outcomes. The development process applied the Rowntree model, consisting of planning, development, and evaluation stages. Data were collected through observation, interviews, questionnaires, expert validation, and pretest–posttest assessments. The product was validated by material, media, and language experts, followed by one-to-one testing, small group trials, and a field test involving 60 students. The effectiveness of the multimedia was analyzed using the N-Gain score. The expert validation results obtained an average score of 89.51%, categorized as very valid. Practicality testing showed high feasibility with student and teacher responses of 92.6% and 93.8%, categorized as very practical. The effectiveness test demonstrated an N-Gain value of 0.79, indicating a high level of effectiveness in improving learning outcomes. The novelty of this study lies in integrating Senjang, an oral cultural heritage of Musi Banyuasin, into interactive multimedia learning, serving not only as a pedagogical tool but also as a medium for cultural preservation aligned with the Merdeka Curriculum and digital learning demands.materials based on local wisdom for the Cultural Arts subject in elementary schools, specifically to enhance students’ understanding of local wisdom at SDN 1 Ulak Paceh, Musi Banyuasin. The development process employed the Rowntree development model, consisting of three main stages: planning, development, and evaluation. The study involved 60 students from SDN 1 Ulak Paceh who participated in pretest and posttest activities, as well as two educators to identify instructional needs. Data were collected through observations, interviews, and questionnaires, and the validity, practicality, and effectiveness of the multimedia materials were evaluated using expert validation, small group trials, and N-Gain analysis. The validation results indicated that the developed interactive multimedia was highly valid with an average expert validation score of 89.51%. The practicality test showed very high practicality levels with small group scores of 92.6% and 93.8%, while the effectiveness test revealed an N-Gain score of 0.79 in the high category, indicating significant improvement in students’ learning outcomes. This research introduces interactive multimedia learning materials integrating local wisdom from Musi Banyuasin, particularly the Senjang cultural element, as a means to preserve regional culture while improving the quality of learning in Cultural Arts subjects at the elementary level.